Study of polyculture fish farming in Kanchanpur district of Nepal - Pant, Janak; Joshi, Sobit; Dawadi, Prava (International Journal of Sustainable Agricultural Research, 2025)
This research examines the study of polyculture fish farming in the Kanchanpur district of Nepal. Fish polyculture has been profitably adopted as a business enterprise in the western part of Nepal, particularly in the Kanchanpur district. Though the number of farmers actively involved in polyculture seems to be increasing, the production trend, productivity, and profitability are not satisfactory. Thus, polyculture study of fish farming was necessary. The research was conducted in various fish farm sites in Kanchanpur district of Nepal. 35 fish farms with a total of 103 ponds were selected for the research. Farm owners were interviewed with pre-tested, semi-structured questionnaires to assess production scale, cost, benefit, production-associated problems, and recommendations. Different fish species, particularly common carp, bighead carp, silver carp, grass carp, rohu, Nile tilapia, and bhakur, were present on the surveyed site. The average area for fish rearing ponds per household was 0.71 ha. The average number of fingerlings per hectare was 22,859. The cost of production includes feed, fertilizer, fingerlings, labor, liming, tools and machinery, investment, construction, and other costs contributing 36%, 3%, 3%, 6%, 0.4%, 2%, 39%, and 9%, respectively, of the total cost of production. The polyculture of carps, tilapia, and bhakur fish species in different polyculture systems was as profitable business enterprises with the productivity of 38.8 quintals/hectare and a benefit-cost ratio of 1.40. Polyculture fish farming was considered a profitable business enterprise in Kanchanpur district with highest B/C ratio, productivity, and benefit per person in carps (Indian and exotic), amongst others.